We exist and resist: peasant women in the south of the Ecuadorian Amazon, facing dispossession processes at the San Carlos Panantza Mega-Mining Project (Research, Society and Development, 2021)
Mega-mining in Ecuador was imposed since the 90s, initially during neoliberal governments, with direct incidence of multilateral organizations such as the World Bank, and later strongly underpinned by the government of Rafael Correa, in the framing of the neo-extractivist agenda of XXI Century Socialism, which promoted medium and large-scale mining projects called emblematic and many others at the hydropower level with the rhetoric of eradicating poverty and resources for Good Living. One of the emblematic projects is San Carlos Panantza, located in the south of the Amazon in the Morona Santiago province in the cantons of San Juan Bosco and Limón Indanza, concessioned to the Chinese company Explorcobres SA belonging to Tonlingt Noun Ferrous Group, and which It is in the advanced exploration stage. This article analyzes the conflicts and psychosocial impacts generated in local communities, and their differential impact on rural women, due to the fact that, due to the roles historically constructed by the patriarchy, care work falls on them. Likewise, it delves into the collective action itineraries that they follow to resist against mega-mining that threatens nature and therefore their livelihoods.